P‐doped random C20 fullerite – model structure for fullerene‐like CPx. Issue 2 (18th October 2012) - Czigány, Zsolt
Abstract Carbon‐based amorphous and fullerene‐like (FL) thin films have a great potential due to their mechanical resiliency. TEM investigation and interpretation of results from FL structures embedded in bulk phases is not straightforward. Here, a model is presented for description of the structure of FL‐CP0.1 thin films and to describe all the rings in the electron diffraction pattern in a self‐consistent way. The model structure consists of random close‐packed and P‐doped C20 clusters resembling a kind of amorphous fullerite (crystals of fullerene cages). The 10% P doping was implemented by creating C18P2 cages by replacing two C atoms by P in the C20 cage. The simulated electron scattering is in agreement with the experimental electron diffraction pattern and reproduces all the observed diffuse diffraction rings of FL‐CP0.1 at ∼1.6, ∼2.6, and ∼5.9 Å. Simulation of HRTEM images confirmed the amorphous appearance of this nanostructured material. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> A cluster of P‐doped random close‐packed C20 fullerite (right) and its calculated electron diffraction (left) for different average cluster size (expressed in number of atoms).